Can we improve clinical outcomes in patients with pneumonia treated with antibiotics in the intensive care unit?. (2nd August 2016) - Nicolau, David P.; Dimopoulos, George; Welte, Tobias; Luyt, Charles-Edouard
ABSTRACT: Introduction : Pneumonia in the intensive care unit (ICU) is associated with high morbidity, mortality and healthcare costs. However, treatment outcomes with conventional intravenous (IV) antibiotics remain suboptimal, and there is an urgent need for improved therapy options. Areas covered : We review how clinical outcomes in patients with pneumonia treated in the ICU could be improved; we discuss the importance of choosing appropriate outcome measures in clinical trials, highlight the current suboptimal outcomes in patients with pneumonia, and outline potential solutions. We have included key studies and papers based on our clinical expertise, therefore a systematic literature review was not conducted. Expert commentary : Reasons for poor outcomes in patients with nosocomial pneumonia in the ICU include inappropriate initial therapy, increasing bacterial resistance and the complexities of IV dosing in critically ill patients. Robust clinical trial endpoints are needed to enable an accurate assessment of the success of new treatment approaches, but progress in this field has been slow. In addition, only very few new antimicrobials are currently in development for nosocomial pneumonia; two potential alternative solutions to improve outcomes could therefore include the optimization of pharmacokinetic/pharmacodynamics (PK/PD) and dosing of existing therapies, and the refinement of antimicrobial delivery by inhalation.